Household Environmental Health Hazards and Child Survival in selected states in India - Journal, IMR (International Multidisciplinary Research Journal, 2014)
Most deaths of children under age five in India and other developing countries have been linked to the household environment. This study, therefore, hypothesized that variation in household environmental conditions (e.g. sources of drinking water, types of toilet facilities, main flooring material of the household, type of cooking fuel) could affect children’s survival chances. Using secondary data from the National Family Health Surveys (NFHS) round 3, the study broadly categorized the eight selected states into low and high under-five mortality groups. Uttar Pradesh, Madhya Pradesh, Bihar and Rajasthan are in the high under –five mortality group whilst Maharashtra, Karnataka, Kerala and Tamil Nadu are in the low mortality group. The dependent variables are under-five mortality and childhood morbidity. Childhood morbidities were measured by the occurrence of diarrhoea, and acute respiratory infection (ARI) within two weeks preceding the survey. The household environmental variables included sources of drinking water, duration of time from water source, types of toilet facilities, main flooring material of the household, type of cooking fuel in the household. The socioeconomic factor was measured with variables such as the mother’s educational level, father’s educational level, rural or urban residence, and household wealth index. The analysis involved the use of descriptive statistics and logistic regression to examine the distribution of household environmental health hazards in each state. The logistic regression model was used to examine the effects of household environmental health hazard on childhood mortality in the selected states.The study found that high-mortality states are at a relative disadvantage on basic household environmental variables. The household environmental conditions had significant influence on child survival. Some of the differences in childhood morbidity and mortality between the two groups can be explained by household environmental health hazards and by mother’s socioeconomic status. In order to meet Millennium Development Goal 4, which requires under-five mortality reduction by two-thirds between 1990 and 2015, attention should be given to various factors affecting the distribution of resources and facilities especially to the high-mortality states. Policy should be redirected to programs that encourage household hygiene and sanitation.